A bankruptcy probability model for assessing credit risk on corporate loans with automated variable selection - Ida Nervik Hjelseth; Arvid Raknerud; Bjørn Helge Vatne (Norges Bank, 2022)
We propose an econometric model for predicting the share of bank debt held by bankrupt firms by combining a novel set of firm-level financial variables and macroeconomic indicators. Our firm-level data include payment remarks in the form of debt collections from private agencies and attachments from private and public agencies and cover all Norwegian limited liability companies for the period 2010-2021. We use logistic Lasso regressions to select bankruptcy predictors from a large set of potential predictors, comparing a highly sparse variable selection criterion ('the one standard error rule') with the minimum cross validation error (CVE) criterion. Moreover, we examine the implications of using debt shares as weights in the estimation and find that weighting has a large impact on variable selection and predictions and, generally, leads to lower out-of-sample prediction errors than alternative approaches. Debt weighting combined with sparse variable selection gives the best predictions of the risk of bankruptcy in firms holding high shares of the bank debt.
hdl:11250/3011180
Keywords: C25; C33; C53; G33; D22; 330; Bankruptcy prediction; credit risk; corporate bank debt; Lasso; weighted logistic regression